Evaluasi Antarmuka Pengguna Pada Proses Booking Online Pendakian Gunung Semeru Dengan Metode Usability Testing - Hiegar Ramadani; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Bromo Tengger Semeru National Park (TNBTS) is a natural conservation area manager who has an original ecosystem, being managed with a zoning system and used for research, science, education, cultivation, culture, tourism and recreation purposes. TNBTS Booking system can provide an alternative to access licensing services online and systematic for Entering Conservation Areas (SIMAKSI). there are many complaints and criticisms about the difficulties in registering the system found on Booking Semeru (bromotenggersemeru.bookingsemeru.org) social media. This research aims to find problems experienced by users when interacting with Booking Semeru using Usability testing methods and interviews with an improvement plan as a comparison form. This study uses 8 respondents classified by 2 types of users based on the intensity of the using system. Results of this improvement study found that the increase in usability testing results from 3,21 of the learnability matrix fell to 1,18. 77.6% from the efficiency matrix increase to 100.0%. The memorability matrix on the initial evaluation of the average number of clicks and the average processing time of 25 clicks and 188 seconds to 15 clicks and 45.25 seconds. 2.84% of the error matrix down to 0%. 43.8 of matrix satisfaction at the initial evaluation rise to 81.9. All results of testing on the interface improvement design compared to Booking Semeru increased in value on each usability matrix.